Impact of Organizational Culture on Job Performance through Administrative Empowerment in Private Hospitals at the Capital City of Sana'a - Al-Genae`e, Nori; Ali, Amr (Jordan Journal of Business Administration, 2021)
The study aimed to identify the impact of organizational culture on job performance through administrative empowerment in private hospitals at the capital city of Sana'a. The study relied on the descriptive analytical approach to achieve its objectives. The data was collected from seven private hospitals through administering a questionnaire to collect the data from a sample of 327 employees. The study findings revealed that organizational culture and administrative empowerment have a positive impact on job performance. It was also revealed that organizational culture has a positive impact on administrative empowerment. Besides, administrative empowerment is considered a partial mediator in the relationship between organizational culture and job performance. The study recommended that there is a need to enhance organizational culture in private hospitals by adopting programs which make organizational culture more visible to their employees. They also should focus on organizational culture and administrative empowerment when designing performance management processes, as they are important factors that contribute to developing job performance.